2009
DOI: 10.1111/j.1526-4610.2009.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Sumatriptan and Naratriptan in Pregnancy: What Have We Learned?

Abstract: The risk of all major birth defects following first-trimester exposure to sumatriptan was 4.6% (95% CI 2.9-7.2%). This coupled with a consistent failure of additional epidemiological studies to observe a signal for major teratogenicity gives a level of reassurance concerning the safety of sumatriptan in pregnancy. There are too few data on naratriptan to draw definitive conclusions, and the sample size for sumatriptan remains too small to detect any but very large increases in specific birth defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 19 publications
1
31
0
6
Order By: Relevance
“…2010 had one study of fluoxetine (71), one of metformin (72), and one of glucose kinetics (73). In 2009, studies addressed dydrogesterone to prevent miscarriage in patients with second trimester vaginal bleeding (74), doxylamine/pyridoxine for nausea/vomiting of pregnancy (75), sumatriptan/naratriptan (76), safety of serotonin reuptake inhibitors (SSRIs)/serotonin norepinephrine reuptake inhibitors (SNRIs) (77), glyburide for gestational diabetes (78), lamotrigine for epilepsy (79), and clonidine (80). The drugs studied in 2008 were sertraline (81), enoxaparin (82), glyburide (83), aspirin in patients whose pregnancy was achieved via IVF (84), and finally midazolam and digoxin (as probe substrates studying CYP3A enzymes and P-glycoprotein) (85).…”
Section: Resultsmentioning
confidence: 99%
“…2010 had one study of fluoxetine (71), one of metformin (72), and one of glucose kinetics (73). In 2009, studies addressed dydrogesterone to prevent miscarriage in patients with second trimester vaginal bleeding (74), doxylamine/pyridoxine for nausea/vomiting of pregnancy (75), sumatriptan/naratriptan (76), safety of serotonin reuptake inhibitors (SSRIs)/serotonin norepinephrine reuptake inhibitors (SNRIs) (77), glyburide for gestational diabetes (78), lamotrigine for epilepsy (79), and clonidine (80). The drugs studied in 2008 were sertraline (81), enoxaparin (82), glyburide (83), aspirin in patients whose pregnancy was achieved via IVF (84), and finally midazolam and digoxin (as probe substrates studying CYP3A enzymes and P-glycoprotein) (85).…”
Section: Resultsmentioning
confidence: 99%
“…23,24 Registry data were also assessed for unusual patterns of defects or trends in birth defect frequency by dose. This paper summarizes the final results of the registry, which closed to enrollment in 2012 after over 16 years (1 January 1996-19 September 2012), updates previously published reports involving fewer pregnancy exposures, 21,22 and provides a summary of the published literature regarding migraine medication use in pregnancy.…”
Section: Introductionmentioning
confidence: 88%
“…7,21,22 However, initial post-marketing surveillance efforts began upon FDA approval of Imitrex in 1992, in response to a request by the FDA for further evaluation of the safety of sumatriptan in pregnancy. In 1993, GlaxoSmithKline (formerly Glaxo) initiated a large post-marketing surveillance study with over 10,000 sites.…”
Section: Introductionmentioning
confidence: 99%
“…These data were obtained from the Sumatriptan and Naratriptan in Pregnancy Registry and may be subject to reporting bias. The authors conclude that the results coupled with lack of epidemiological evidence to support a strong association are reassuring since the reported rates compare favorably with the 3-6% background rate at 5 years of age [49,52 ]. Furthermore a thorough review of triptan use in pregnancy found that the available literature does not support different perinatal or pregnancy outcomes for patients exposed to triptans after conception [51].…”
Section: Antidepressants Amitriptylinementioning
confidence: 76%